Application of virtual simulation technology in sports decision training: a systematic review - Yunchao, Ma; Mengyao, Ren; Xingman, Li (Frontiers in Psychology, 2023)
Sports decision-making is a complex process and plays a decisive role in sports performance. Virtual simulation technology is one of the popular sports decision-making training tools. The application of virtual reality technology in sports decision-making training has received widespread attention. The purpose of this study is to evaluate the scientific evidence of the application of virtual simulation technology in sports decision-making training, and summarize its application advantages and limitations. The research literature databases of PubMed, Web of Science, CNKI, PsycINFO, SportDiscus, and IEEE Explore were searched. Key words with different combinations of ‘Virtual Reality’ and ‘Sport Decision-making’ were used. The results were screened by two aythors independently to determine the application of virtual reality technology in motion decision-making. 10 articles were identified and coded to record the research design, research object characteristics, VR task setting, experimental intervention and research results. Through the review, it is found that virtual simulation technology has important value for sports decision-making training. In sports practice, virtual simulation technology can simulate sports decision-making tasks, measure and analyze athletes' sports decision-making performance. We still need to design a more scientific virtual simulation environment for sports decision-making. In this environment, we can better use virtual simulation technology to improve sports decision-making ability.